Pengenalan Teknologi Mikrokontroler Arduino Dalam Pembelajaran Fisika Di SMA Negeri 10 Ambon - frandy akyuwen; Fredrik Manuhutu; Ledy Manuhutu; Grimaldy Rooy Latumeten; Sufilman Ely; Gianita Anastasia Salamena; Poltjes Pattipelohy (PELITA NUSA TENGGARA, 2026)
The development of digital technology demands innovation in physics learning to make it more contextual and applicable. However, in it’s implementation, learning at the Senior High School (SMA) level still faces various problems, especially in physics learning. One of the main obstacles is the abstract and mathematical nature of physics material, making it difficult for students to understand if it is only delivered through lecture methods or text-based learning. This community service activity aims to introduce Arduino microcontroller technology as a practical-based physics learning medium to improve students conceptual understanding and interest in learning. The activity implementation method is designed gradually and participatively, including preparation stages, socialization and introduction to Arduino concepts, training and physics practicum based on Arduino, as well as evaluation and follow-up. The participants consisted of 20 twelfth-grade science major students from SMA Negeri 10 Ambon. Evaluation was conducted using a questionnaire instrument to assess students perceived understanding, interest, and responses to the activity. The results showed an increase in students perceived understanding of physics concepts after the activity, with 55% categorized as “very good” and 35% as “good.” In addition, students interest and enthusiasm for Arduino-based physics learning also increased, reaching 70% in the “very good” category. These findings indicate that the use of Arduino microcontrollers is effective as an interactive and contextual physics learning medium, with the potential to improve the quality of physics education in schools.